Entrepreneurship Education and Family Support as Predictors of Entrepreneurial Intention: The Mediating Role of Entrepreneurial Experience among University Students - Patriandi Nuswantoro (CV. Sakura Digital Nusantara, 2025)
This study aims to analyze the influence of entrepreneurship education and family support on students’ entrepreneurial intention, with entrepreneurial experience as a mediating variable. A quantitative approach was employed using Path Analysis. Data were collected from 108 university students through an online questionnaire distributed via Google Forms, utilizing a Likert scale to measure four main variables: entrepreneurship education, family support, entrepreneurial experience, and entrepreneurial intention. Respondents were selected using a probability sampling technique. The results indicate that entrepreneurship education does not have a direct significant effect on entrepreneurial intention but has a positive influence on entrepreneurial experience. Family support shows a positive effect on both entrepreneurial experience and entrepreneurial intention. Furthermore, entrepreneurial experience positively affects entrepreneurial intention and serves as a mediator in the relationship between entrepreneurship education and family support on entrepreneurial intention. These findings highlight the crucial role of entrepreneurial experience as a bridge between entrepreneurial learning and family support in shaping students’ motivation to pursue entrepreneurship.